Некоторые итоги изучения сельской округи античного Нимфея - Зинько, В.Н. (Материалы по археологии, истории и этнографии Таврии, 1996)
This article dwells on the results of the research of archaeological monuments of rural neighbourhood of the ancient city of Nimphei. The author has summarized the materials of archaeological research undertaken by 1.1. Kruglikova and V.A.Goroncharovski in this district and gives much new data about settlements, cemeteries and remains of delimitation obtained during his own excavation and reconnaissance in recent years. On the basis of archaeological materials and written sources, chronological periods of rural monuments of Nimphei are given. In general, despite insufficient study of monuments, some chronological gaps, it is noted that life in rural neighbourhood of Nimphei had continued during the whole antique epoch. The main moments of it are correlated with general development of rural territories of whole European Bosporos. At the same time some definite peculiarity as a result of specific role of Nimphei on the first stage of existence, outside Bosporos tyranny, showed up. The final phase of antique epoch is of special interest because rural monuments of this period were known only in Kerch Azov region.